SEMAGLUTIDE AND BODY COMPOSITION: A NARRATIVE REVIEW OF ITS EFFECTS ON LEAN MASS AND STRATEGIES FOR PRESERVATION - Anna Tomasiewicz; Jan Zabierowski; Maciej Pachana; Piotr Kukuła; Marcin Piersiak; Hubert Sawczuk; Julia Marschollek; Maciej Ziomek (International Journal of Innovative Technologies in Social Science, 2025)
In recent years a steady increase in the prevalence of obesity has caused a growing interest in pharmacological anti-obesity treatment, including semaglutide, glucagon-like peptide-1 (GLP-1) receptor agonist, which has been proven effective in inducing weight loss in obese patients. However, due to rapid growth of its popularity, monitoring and updatig of guidelines and potential adverse effects may have been outpaced. One of the adverse effects taken into consideration is semaglutide’s impact on reduction of lean mass, fat-free mass and muscle mass. Available studies, although not unanimous, indicate that although decrease of lean mass occurs alongside loss of fat mass, proportion of lean mass increases. Moreover, some studies suggest that semaglutide treatment has a positive impact on muscle function. Nevertheless, the search for strategies allowing for mitigation of lean mass loss during this treatment is still necessary, particularly considering groups of patients at risk of such a complication. Two approaches are being considered: lifestyle interventions and pharmacological treatment. Studies suggest that resistance exercise training interventions can elicit significant increases in lean mass during semaglutide treatment. When it comes to dietary interventions, there is significant need for research that would aim at identifying dietary factors promoting lean mass preservation in this population. Currently explored pharmacological support options include various human monoclonal antibodies (bimagrumab, trevogrumab, garetosumab). Introducing these drugs alongside semaglutide has promoted lean mass preservation despite fat mass loss. Currently existing studies should serve as a guide for further extensive research. At this time, it seems there are more questions than answers surrounding the issue of semaglutide’s impact on lean mass and strategies to mitigate its excess loss.